Meningkatkan Hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Kekuatan Dua yang Dibantu Media Interaktif dalam Pengajaran Bahasa Indonesia di Sekolah Dasar - Nailul Amna; Rafidhah Hanum; Yuni Setia Ningsih; Cut Atthahira; Azhar Azhar (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2026)
The quality of learning outcomes in Indonesian language education at the elementary level remains a persistent challenge, particularly in the domain of reading comprehension. This study investigates the effectiveness of the Power of Two cooperative learning model supported by interactive digital media in improving student learning outcomes in Indonesian language instruction. Employing a Classroom Action Research (CAR) design based on the Kemmis and McTaggart cyclical model, the study was conducted over two cycles with 22 fourth-grade students at an Islamic elementary school in Banda Aceh, Indonesia. Data were collected through structured observation sheets and end-of-cycle achievement tests, then analyzed using descriptive quantitative techniques. Results demonstrated substantial gains across all measured dimensions: teacher activity scores improved from 70.31% (adequate) to 89% (good), student activity scores rose from 65.62% to 86.40%, and overall learning mastery advanced from 54.54% in Cycle I to 81.81% in Cycle II. The average student score increased from 66.81 to 83.63, surpassing the minimum mastery threshold of 75. These findings confirm that integrating the Power of Two model with interactive media creates a more engaging, collaborative, and effective learning environment. The study contributes to the growing body of evidence supporting cooperative and technology-enhanced learning strategies in early formal education, with implications for curriculum design and pedagogical innovation across diverse school settings.